ECONOMIC EFFICIENCY OF MANAGEMENT INFORMATION SYSTEMS AT ENTERPRISES - BENZERUK, Vitalii; PROKOPENKO, Nataliia; KOVALENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The scientific article analyzes the economic efficiency of information management systems at enterprises, which is a topical topic in the conditions of a dynamic market environment. The purpose of the study is to assess the impact of management information systems on key performance indicators of enterprises, such as productivity, costs and quality of customer service. It is important to note that management information systems are designed to solve the tasks of strategic and tactical planning, operational management, as well as control and accounting. With their help, you can optimize management processes and reduce the costs of secondary data processing, which is an important aspect for improving the overall efficiency of the enterprise. The use of management information systems allows not only to increase the competitiveness of enterprises, but also to reduce the complexity of management decision-making, to improve the reliability of information, which, in turn, contributes to objective financial decision-making. The active use of information technologies in business management has a positive effect on operational efficiency, providing flexibility in response to changes in the market environment. The study shows that the economic efficiency of management information systems is directly related to their ability to optimize business processes, reduce costs and increase productivity. The implementation of information management systems facilitates the automation of routine tasks, which allows employees to focus on more important aspects of the activity, improving overall performance. Thanks to this, enterprises are able to adapt faster to new economic challenges and better predict market needs. Particular attention should be paid to the influence of management information systems on the quality of customer service. Management systems allow faster processing of requests, which positively affects customer satisfaction and their loyalty. For a comprehensive analysis of the economic efficiency of information management systems, it is important to determine key indicators, such as return on investment, payback time of implementation, and labor productivity. The analysis of these indicators helps to identify optimal directions for investments and improvement of systems. The conclusions of the article confirm that management information systems are important tools for increasing efficiency, competitiveness and long-term development of enterprises in modern conditions.